COVID-19 in Ghana: Knowledge, perception and practice among health trainees - Adu, David Kwabena; Gyan, Bernard; Dzokoto, Maxwell Kwame; Addai, Richard; Woli, Moses Kofi; Boamah, Bismark; Puplampu, Paapa; Ofori, Emmanuel; Baffoe, Augustine; Bonsu, Albert; Opoku-Adusei, Kwabena (Open Science Journal, 2020)
Objective: This study assessed the knowledge, perceptions and practices among health trainees in Ghana regarding COVID-19. Understanding the knowledge, perception and practices among health trainees can provide important information for policy formulations and proper planning. Method: The survey was conducted through a Google form link shared on students’ social media networks mainly through Facebook, and WhatsApp platforms. Responses received were imported to SPSS version 24 for cleaning and analysis. Output measures were demonstrated in simple frequency and percentages, using tables and charts. Fisher’s exact test was used to assess the effect of potential covariate on practice of preventive measures with their corresponding p-values. Results: Twenty-five percent (25%) of respondents had good knowledge, 69% had moderate knowledge and 6% had poor knowledge on COVID-19. Regarding perception of health students on COVID-19, 8.47% indicated that drinking alcohol could protect them from the virus. More than 90% of participants’ practice the general preventive measures. Gender and level of program of study was found to be significantly associated with practice of preventive measure. Male students (54.64%) were engaged in good preventive practices compared to female students (43.75%). Conclusion: Majority of the health trainees had basic information and proactive practice towards COVID-19. Most trainees had good perception on the disease, however, a few still believe that drinking alcohol will prevent them from being infected with the disease. Gender and level of trainees are significant predictors of proactive practices towards COVID-19.